2022
DOI: 10.1111/sltb.12852
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationships between muscle dysmorphia symptoms and suicidal ideation

Abstract: Introduction: Muscle Dysmorphia (MD) is a severe subtype of body dysmorphic disorder (BDD) that shares symptomatic overlap with eating disorders. Although associations between eating disorders/BDD and suicidality are well documented, research has rarely examined associations between MD symptoms and suicidality, which is concerning given MD is associated with additional suicide risk factors compared with these disorders. Further, existing associations between MD symptoms and suicidality have yet to establish te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
2
4
1
1
Order By: Relevance
“…The findings from this study align with prior research among the US men that have shown that muscle dysmorphia symptomatology is associated with suicidal ideation (; Grunewald, Ortiz, et al, 2022;Ortiz et al, 2021). This prior research also found that there was a positive longitudinal relationship between suicidal ideation and Appearance Intolerance (Grunewald, Ortiz, et al, 2022;Grunewald, Troop-Gordon, & Smith, 2022), which Note: Each cell represents the abbreviated outputs of 48 separate modified Poisson regression models with muscle dysmorphia symptomatology (measured using the MDDI total score and three subscales in separate models) as the independent variables and suicidal thoughts, suicidal behaviors, and NSSI as the dependent variables (in separate models). Boldface indicates statistical significance using the Benjamini-Hochberg procedure with a 10% false-discovery rate.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings from this study align with prior research among the US men that have shown that muscle dysmorphia symptomatology is associated with suicidal ideation (; Grunewald, Ortiz, et al, 2022;Ortiz et al, 2021). This prior research also found that there was a positive longitudinal relationship between suicidal ideation and Appearance Intolerance (Grunewald, Ortiz, et al, 2022;Grunewald, Troop-Gordon, & Smith, 2022), which Note: Each cell represents the abbreviated outputs of 48 separate modified Poisson regression models with muscle dysmorphia symptomatology (measured using the MDDI total score and three subscales in separate models) as the independent variables and suicidal thoughts, suicidal behaviors, and NSSI as the dependent variables (in separate models). Boldface indicates statistical significance using the Benjamini-Hochberg procedure with a 10% false-discovery rate.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, prior research has documented that body dissatisfaction is a predictor of suicidal ideation (Perkins & Brausch, 2019;Rufino et al, 2018). Interestingly, however, the current study did not find any positive association between Drive for Size and suicidal thoughts and behaviors, which was positively associated in prior research (Grunewald, Ortiz, et al, 2022;Grunewald, Troop-Gordon, & Smith, 2022). It may be that the specific means to pursue muscularity (i.e., weight training and exercise) act as protective factors for suicidal thoughts and behaviors.…”
Section: Discussioncontrasting
confidence: 87%
“…Individuals could participate if they were in the United States, 18 or older, and reported two or more MD symptoms over the past 28 days. The protocol for this study is described in published manuscripts (Grunewald, Kinkel‐Ram, et al, 2022; Grunewald, Ortiz, et al, 2022); however, current aims are unique to this study. Additional methodological considerations can be found in Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…That is, specific MDDI subscales may have been associated with lifetime suicide attempts. In fact, recent research has shown that specific MDDI subscales are related to increased suicidal ideation severity among men with subclinical MD symptoms, but these relationships disappear when using the MDDI total score (Grunewald et al, 2022 ). While running a model with all three MDDI subscales was not feasible due to concerns regarding power and raising error rates, future research should test these subscales individual relations with the other variables in the model.…”
Section: Study 2: Discussionmentioning
confidence: 99%